Sponges architecture by colour: new insights into the fibres morphogenesis, skeletal spatial layout and morpho-anatomical traits of a marine horny sponge species (Porifera). Issue 1 (1st January 2021) - Stocchino, G. A.; Cubeddu, T.; Pronzato, R.; Sanna, M. A.; Manconi, R.
Abstract: This paper focuses on the skeletal architecture and morphotraits of the Mediterranean horny sponge Sarcotragus spinosulus (Demospongiae, Keratosa, Dictyoceratida, Irciniidae). This special endoskeletal system consists of a dense, variably complex connective architecture, which extends throughout the entire sponge body and is embedded in an abundant jelly-like extracellular matrix (ECM). To investigate the topographic arrangement and micro-morphotraits of these connective structures in detail and by colour, also during morphogenetic processes, histology techniques using light microscopy are essential. New information is provided on the coordinated morphogenetic processes that characterize the growth and assembly of collagenic prototype structures in the matrix of fibrous skeletal elements and drive skeleton remodelling. Our results also highlight some novelties and some remarkable peculiarities of fibrous, filamentous and fibrillar components at the levels of both composition and structure. The morphofunctional significance of skeletal architecture is suggested in the background of the anatomical complexity of S. spinosulus .